Complexity as Interrelatedness: an Input-Output Approach - Amaral, João Ferreira do (2009)
In this paper we make a first attempt to link two subjects with a potentially useful, but as yet not conveniently explored, connection: the study of complexity and the (Leontief) input-output analysis. In this context, we consider economic complexity as interrelatedness between the different parts or sectors of an economy, as represented by an input-output system and one interesting question emerges, namely: should we expect to find a natural move to higher complexity as the economy grows and develops? And a related one: is a larger economy necessarily more complex than a smaller one? In a first attempt to answer these questions we propose a new measure of complexity as interrelatedness that combines a network effect and a dependency effect. In the empirical part of the paper we apply this measure of complexity to the inter-industry tables of several OECD countries, and discuss some interesting findings.